2001
DOI: 10.2308/aud.2001.20.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Additional Evidence on Audit Report Lag

Abstract: The process for providing accounting information to the public has not changed much in the last century even though the extent of disclosure has increased signifi-cantly. Sundem et al. (1996) suggest that the primary benefit of audited financial statements may not be decision usefulness but the discipline imposed by timely confirmation of previously available information. In general, the value of information from the audited financial statement will decline as the audit report lag (the time period between a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
290
3
16

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(342 citation statements)
references
References 9 publications
8
290
3
16
Order By: Relevance
“…More sophisticated investors may obtain substitute sources of information and thus incur higher costs as earnings announcements are delayed. The literature on earnings quality suggests that unexpected reporting delays may be associated with lower quality information (Knechel & Payne, 2001). What is clearly evident from prior studies is that good news is announced earlier than bad news.…”
Section: A Good News Early and Bad News Latesupporting
confidence: 48%
See 1 more Smart Citation
“…More sophisticated investors may obtain substitute sources of information and thus incur higher costs as earnings announcements are delayed. The literature on earnings quality suggests that unexpected reporting delays may be associated with lower quality information (Knechel & Payne, 2001). What is clearly evident from prior studies is that good news is announced earlier than bad news.…”
Section: A Good News Early and Bad News Latesupporting
confidence: 48%
“…The more diverse and complex the client's operations, the greater the amount of audit work that must be performed (Newton & Ashton, 1989;Bamber et al, 1993;Whittred, 1980;Butler et al, 2004;Knechel & Payne, 2001). We expect the number of segments (NUM), extraordinary items (EXTR), negative earnings (LOSS), and an auditor's opinion (OPIN) to be positively related with LAG (Ashton et al, 1987;Schwartz & Soo, 1996).…”
Section: Audit Related Factormentioning
confidence: 99%
“…Consistent with prior literature [3,17], audit delay or audit reporting lag is measured as a function of the number of days that elapse from the closure of the accounting period until the date of the audit report. In order to investigate the association between audit reporting lag and selected independent variables, the following model is developed:…”
Section: Methodsmentioning
confidence: 59%
“…For example, Newton and Ashton (1989), Bamber et al (1993), and Jaggi and Tsui (1999) all documented that structured audits tended to have longer ARL. On the other hand, Knechel and Payne (2001) found that more audit testing procedures completed by the public accounting firm in advance of the annual audit (i.e., interim testing) was associated with improved timeliness.…”
Section: Auditor Changesmentioning
confidence: 99%
“…Knechel and Payne (2001), Lee et al (2009), and all documented a negative association between non-audit services and ARL, indicating that non-audit services may create knowledge spillover benefits that result in shorter ARL. However, observed that this association no longer appears to be present for US companies following the passage of SOX, and that companies that paid higher non-audit fees prior to SOX experienced greater ARL following SOX.…”
Section: Audit Firm Characteristicsmentioning
confidence: 99%